Identification and Comparison of Chemosensory Genes in the Antennal Transcriptomes of Eucryptorrhynchus scrobiculatus and E. brandti Fed on Ailanthus altissima - Wen, Xiaojian; Wang, Qian; Gao, Peng; Wen, Junbao (Frontiers in Physiology, 2018)
The key to the coexistence of two or more species on the same host is ecological niche separation. Adult Eucryptorrhynchus scrobiculatus and E. brandti both feed on the tree of heaven, Ailanthus altissima, but on different sections of the plant. Olfaction plays a vital role in foraging for food resources. Chemosensory genes on the antennae, the main organ for insect olfaction, might explain their feeding differentiation. In the present study, we identified 130 and 129 putative chemosensory genes in E. scrobiculatus and E. brandti, respectively, by antennal transcriptome sequencing, including 31 odorant-binding proteins (OBPs), 11 chemosensory proteins (CSPs), 49 odorant receptors (ORs), 17 ionotropic receptors (IRs), 19 gustatory receptors (GRs), and three sensory neuron membrane proteins (SNMPs) in E. scrobiculatus and 28 OBPs, 11 CSPs, 45 ORs, 25 IRs, 17 GRs, and three SNMPs in E. brandti. We inferred that EscrOBP8 (EscrPBP1), EscrOBP24 (EscrPBP2) and EbraOBP8 (EbraPBP1), EbraOBP24 (EbraPBP2) were putative PBPs by the phylogenetic analysis. We identified species-specific OR transcripts (10 EscrORs and 8 EbraORs) with potential roles in the recognition of specific volatiles of A. altissima. In addition to conserved “antennal IRs”, we also found several “divergent IRs” orthologues in E. scrobiculatus and E. brandti, such as EscrIR16, EbraIR19, and EbraIR20. Compared with other chemosensory genes, GRs between E. scrobiculatus and E. brandti shared lower amino acid identities, which could explain the different feeding habits of the species. We examined OBP expression patterns in various tissues and sexes. Although amino acid sequence similarities were high between EscrOBPs and EbraOBPs, the homologous OBPs showed different tissue expression pattern between two weevils. Our systematic comparison of chemosensory genes in E. scrobiculatus and E. brandti provides a foundation for studies of olfaction and olfactory differentiation in the two weevils as well as a theoretical basis for studying species differentiation.